Interfacial Electron Transfer in Dye-Sensitized TiO2 Devices for Solar Energy Conversion - Müller,Andressa V. (2021)
The development of cost-effective molecular devices that efficiently capture and convert sunlight into other useful forms of energy is a promising approach to meet the world’s increasing energy demands. These devices are designed through a successful combination of materials and molecules that work synergistically to promote light-driven chemical reactions. Light absorption by a surface-bound chromophore triggers a sequence of interfacial electron transfer processes. The efficiencies of the devices are governed by the dynamic balance between the electron transfer reactions that promote energy conversion and undesirable side reactions. Therefore, it is necessary to understand and control these processes to optimize the design of the components of the devices and to achieve higher energy conversion efficiencies. In this context, this review discusses general aspects of interfacial electron transfer reactions in dye-sensitized TiO2 molecular devices for solar energy conversion. A theoretical background on the Marcus-Gerischer theory for interfacial electron transfer and theoretical models for electron transport within TiO2 films are provided. An overview of dye-sensitized solar cells (DSSCs) and dye-sensitized photoelectrosynthesis cells (DSPECs) is presented, and the electron transfer and transport processes that occur in both classes of devices are emphasized and detailed. Finally, the main spectroscopic, electrochemical and photoelectrochemical experimental techniques that are employed to elucidate the kinetics of the electron transfer reactions discussed in this review are presented.